An Investigation into the Effect of Written Corrective Feedback on the Performance of Intermediate Writers of English - Maryam Vazifeshenas (PT. Pusmedia Group Indonesia, 2025)
In the last three decades, several researchers have investigated the effects of corrective feedback on language learners’ oral and writing performance. The mixed results of the empirical studies conducted by scholars throughout the world calls for more investigations to uncover the unknown aspects of corrective feedback. The present study attempted to disclose the benefits of written corrective feedback by comparing its effects with those of the oral corrective feedback. The present study focused on different writing components which are content, organization, language use, vocabulary, and mechanics. Thirty-four intermediate English language learners of two intact classes, who were selected based on convenience sampling, participated in this study. The students of one of these classes received oral corrective feedback and the students of the other class were provided with written corrective feedback. The results indicated that both oral and written corrective feedback improved second language students’ writing ability. However, written corrective feedback was significantly more successful in improving the participants’ writing ability. The findings also indicated that written corrective feedback was significantly superior to oral corrective feedback in the three areas of organization, language use, and mechanics. In the two areas of vocabulary and content, the differences were not significant, however.